Case report: 10 years follow-up of psychosis due to Fahr’s disease complicated by a left temporal stroke - De Pieri, Marco; Poglia, Greta; Bartolomei, Javier (Frontiers in Psychiatry, 2023)
Fahr's disease (FD) is a rare disorder, characterized by basal ganglia calcification and presenting with movement disorders, speech impairment, cognitive deficits and neuropsychiatric symptoms.Psychotic disorders related to FD are barely described in the literature and a knowledge is missing concerning pathophysiology, course and management. Here we report on the long-term follow-up of a patient who had 3 acute episodes of FD-psychosis characterized by bizarre delusions and behavioral disorganization, without hallucinations. Genetic and metabolic causes of FD were ruled out. In all three episodes an olanzapine monotherapy rapidly and completely resolved psychosis, without inducing metabolic syndrome and extrapyramidal symptoms. Besides the acute decompensations, the patient presented a tame, introverted, industrious and perfectionistic personality, that we could interpret as the "parkinsonian personality" described for many other basal ganglia disorder. Moreover, bizarre appearance, reduced affectivity, abulia, concrete speech and a stiff motricity in the context of a mild asymmetric extrapyramidal syndrome characterized the mental status. Cognitive profile was initially marked by executive difficulties and partial agnosia, with an IQ of 86. Ten-years in the course, the patient suffered from an ischemic stroke in the left superior temporal gyrus, which provoked a decline in memory and executive functions, without any impact on the psychiatric picture. An antiphospholipid antibody syndrome emerged as the underlying cause; thus, for the first time in the literature an overlap of FD and antiphospholipid antibody syndrome is described here. This case report stresses once more the need for a better integration of psychiatry and neurology and for the investigation of secondary causes of late-onset psychosis.